A most noble heir [large type] - Mason, Susan Anne (Thorndike Press, a part of Gale, a Cengage Company, 2018)
When stable hand Nolan Price learns from his dying mother that he is the son of the Earl of Stainsby, his plans for a future with kitchen maid Hannah Burnham are shattered. As Nolan struggles to learn the ways of the aristocracy, he finds himself caught between pleasing Hannah and living up to his father's expectations.